(untitled) (International Journal of Innovative Research in Engineering & Management, 2024)
In modern era, concrete is widely used in building material. Concrete is durable, strong and locally available. It has a property of resisting the compressive load to a limit but if the load applied goes beyond the limit, the strength of concrete is reduced because of the development of the cracks in the concrete. Thus the treatment for these cracks becomes very expensive. The development of cracks in concrete affects the serviceability limit of concrete. The influx of water and harmful chemicals into the concrete may decrease both the strength and life. Structural failure may be caused by micro-cracks. One way to avoid costly manual maintenance and repair is to include an autonomies self-healing mechanism in concrete. One such an alternative mechanism is correctly being studied i.e. a novel technique based on the application of bio-mineralization of bacteria in concrete. The applicability of specifically calcite mineral precipitating bacteria for concrete repair and plugging of pores and cracks in concrete has been investigated and studies on the possibility of using specific bacteria as a sustainable and concrete embedded self-healing agent was studied and results from ongoing studies are discussed. Synthetic polymers such as epoxy treatment etc. are now a days used for repair of concrete are harmful to the environment, hence the biological repair technique is focused. Recently, it has been found that microbial carbonate Precipitation resulting from the metabolic activities of micro-organisms in concrete modified the overall behavior of concrete. Hence, in this paper, we explain the bacterial concrete, its classification and types of bacteria, chemical processes to fix the micro cracks, advantages ,disadvantages and the possibilities on application of micro-organisms in the concrete. The different strengths of normal concrete and concrete with bacillus were analyzed and the tests were conducted and compared.